Daily low-dose of Tadalafil improves pain and frequency in Bladder pain syndrome/Interstitial cystitis patients - José Luís Simães Mendes Ferreira da Costa (2020)
Daily low-dose of Tadalafil improves pain and frequency in Bladder pain syndrome/Interstitial cystitis patients José Simães a, Pedro Abreu-Mendes a b, Pedro Pereira b, Nuno Dias b, Francisco Cruz a b c, Paulo Dinis a b c, Rui Pinto a b c a Faculdade de Medicina da Universidade do Porto b Departamento de Urologia CHU São João c I3s - i3S Institute Investigation and Innovation in Health Porto, Portugal Abstract: INTRODUCTION AND OBJECTIVE: Bladder Pain Syndrome/Interstitial Cystitis (BPS/IC) is a chronic inflammatory disease characterized by suprapubic pain associated with other lower urinary tract symptoms: increased frequency, urinary urgency, and nocturia. Increasing evidence suggests that bladder afferent hyperexcitability, through neurogenic bladder inflammation and urothelial dysfunction, plays a key role in the pathophysiology of BPS/IC. The rationale of using phosphodiesterase type 5 inhibitors (PDE5i) would be to hinder cyclic guanosine monophosphate cGMP pathway and decrease bladder afferent hyperactivity. Consequently, relaxation of the detrusor, improvement of microcirculation and decreasing adrenergic nociceptive overactivity would be noted. We aimed to evaluate efficacy, tolerability, and safety of a daily low dose of 5 mg tadalafil in refractory BPS/IC patients. METHODS: A total of 13 refractory BPS/IC female patients, previously evaluated with a physical examination, bladder diary, bladder-pain related visual analog score (VAS), O'Leary-Sant Scores (OSS) for symptoms and problems and quality of life (QoL) question from IPSS, were treated with a daily low-dose of tadalafil (5 mg, oral) for 3 months. Patients were evaluated after 4 and 12 weeks, for the same parameters. Adverse events and urinary tract infections were also assessed. Results are shown as mean values ± standard deviation. T-test was used for comparisons. RESULTS: BPS/IC patient's age was 43±13 years. At baseline, pain intensity in VAS (0-10) was 6.7±1.4, OSS was 25,7±4,3, day and night frequency were 12,6±5,2 and 4,4±2,7, respectively; maximal bladder capacity (CC) was 185,7±56.9 ml and QoL score (0-6) was 5±1. Urinary frequency, OSS and QoL were significantly improved at 1-month follow-up (10±2.5, 21,9±4,1 and 4±1,5, respectively, p<0.05). Pain intensity and volume voided were significantly improved at a 3-month follow-up (3,5±2 and 266,7±60,5, p<0.05). Patients referred to urinary frequency as the most important reported parameter improved at 1-month follow-up and pain at 3 months. Seven patients had Hunner's lesions but there were no differences between ulcer and non-ulcerated patients. Two patients dropped out due to unsatisfactory results and 2 due to persistent headache and/or tachycardia. No urinary tract infections were reported, during the trial. CONCLUSIONS: Daily low-dose tadalafil is an easy, well-tolerated and effective treatment for refractory BPS/IC in women.